CONSERVATION OF MINIMALLY PROCESSED MANGO TOMMY ATKINS BY APPLYING AN ALOE VERA (ALOE BARBANDENSIS MILLER) COATING - Pérez T., Andrés Felipe; Aristizábal, Iván D.; Restrepo F., Jorge I. (Vitae, 2016)
Background: Mango is a climacteric fruit which can limit its marketing due to some deficiencies in processing and preservation systems that cause postharvest losses in the agribusiness and value chain. Minimally processed fruits and edible coatings represent an alternative to decrease the perishability of fruits, preserving its quality attributes and offering to consumers an easy product to use and storage. Objetives: The aim of this study was to conserve and extend the shelf life of minimally processed “Tommy Atkins” mango covered by an edible coating made of aloe vera mucilage, assessing its effectiveness by analyzing physical, physicochemical, respiratory, microbiological and sensory parameters during refrigerated storage. Methods: The edible coating was prepared with aloe vera, which is a mucilaginous gel, in a concentration of 50% w/w in dilution and homogenized with carnauba wax and glycerol. Then aloe vera was applied by immersion in the pre-cut fruits and dried in stove. Four experimental treatments were designed: C, R, PreREC and CA, stored under refrigeration for a period of 12 days, in which parameters such as strength, color, percentage weight loss, pH, Brix, acidity (%), respiratory rates, microbiological counts, and sensory descriptors were evaluated by a multidimensional approach profile. Data were analyzed using ANOVA and the LSD multiple comparison method. Results: Samples treated with the edible coating (R y PreREC) showed a delay in the loss of firmness, less color changes, less loss of weight, a less increase in pH and Brix values, and a higher acidity compared to the control treatments. Low rates of O2 consumption and controlled CO2 production compared to untreated samples were achieved. Coating decreased the growth of mesophilic, molds and yeasts; while sensory descriptors as firmness, overall quality, characteristic odor and taste showed a higher rating by the sensory panel. Conclusions: Edible coating made of aloe vera gel allowed to keep for 3 more days samples of minimally processed mango compared to control treatments.